Efeito da terapia com laser de baixa intensidade em estudo clínico e experimental de asma brônquica - Soares, Clariana Rodrigues (2017)
Bronchial asthma affects more than 300 million people worldwide and poses a large socioeconomic burden and over 100 million new asthma patients will be present worldwide by 2025. The morbidity and mortality rate remain at unacceptable levels; associated hospitalization rate and medical costs are still on the upsurge as well. Overreliance on medication and associated adverse drug effects have led to exploration of alternative management modalities. Photobiomodulation therapy (PBMT) has been used in experimental and clinical studies for the treatment of inflammatory diseases. The literature using Low-level laser therapy (LLLT) has been reported against inflammatory diseases, such as chronic hypertension and in autoimmune problems as well as cicatrization processes in major surgeries. Some papers had been employed modulating pro and anti- inflammatory cytokines in secure matter with success in acute lung disorders. The LLLT can relieve the late and early symptoms of airway and lung inflammations by reducing inflammatory mediators. The aim of this study was to evaluate LLLT response in animal’s models and in patients with bronchial asthma. This work was divided in 2 phases: Phase 1- Translational Clinical Study and Phase 2 – Experimental Model. In the 1st part a pilot study (Protocol 1) were done for dose determination and the 2nd. Patients were their own controls. For all patients the sputum analysis induced by flow cytometry and cytokines evaluation by ELISA were colleted. The study was divided in two phases. Phase1 was a case study: CW Diode Laser Ga-Al-As (Gallium-Aluminum-Arsenide, ʎ=660 nm, P=30 mW, fluence=15 J/cm2, total energy= J; time= 20 sec irradiation for each point). A 16 spots into mucosa of mouth and intra nasal region were irradiated. In this first part, the treatment was 10 weeks of applications, once a week. The 2nd Protocol consisted of clinical study with 6 patients. 1st irradiation: Diode Laser (ʎ=660nm, P=35 mW fluence=26,3 J/cm2, 30 sec irradiation for each point) and a 2nd irradiation: (ʎ =780nm, P= 35 mW, fluence=26,3 J/cm2, total energy= J; time= 30 sec irradiation for each point). In this cases the treatment was twice a week, one application with red laser at 660 nm wavelength and another with infrared at 780 nm wavelength on the same day, totaling 22 irradiated points. It was in total of 5 weeks applications. All patients were reevaluated after 5 sessions by sputum analysis induced by flow cytometry and cytokines evaluation by ELISA. Phase 2 : Experimental Study. The groups consisted on 52 animals, divided in 5 groups, as: No manipulation Group (Basal), challenge animals with ovoalbumina (OVA(72)), challenge animals with OVA and irradiation with LLLT (OVA+L/ 72h), challenge animals desafiados with OVA and irradiation with LLLT and laser application were interrumpted for a week before eutanasia. (OVA+L(1s), challenge animals with OVA and LLLT was applied and laser application were interromped for 2 weeks before eutanasia (OVA+L(2s)). It was employed into mouses, as it was described in following matter: 1° (λ- 660nm, P- 100 mW, T- 30 s per point); 2° (λ- 808nm, P- 100mW, T- 30 s per point). Our experimental data also corroborated the photobiomodulation effects as it was pointed out from the literature. Our work showed that LLLT was able to reduce significantly the total number of cells, macrophages, eosinophils and increased CD4 T lymphocytes in induced sputum. Besides, there was an increase in the levels of IL-10 and IFN-γ in the patients’ sputum supernatant. Our animals’ data indicated some signals of mechanism action involved in patients; therefore it was possible to conclude that the photobiomodulation therapy had favorable effects both in animals and human beings. Thus, this study may contribute to the asthma treatment, with no side effects, a non-invasive and cost effectiveness treatment that may be adoptated for health police in our country.